Optimal Sales Force Compensation in Dynamic Settings: Commissions vs. Bonuses - Schöttner, Anja (Management Science, 2017)
This paper studies optimal sales force compensation plans in a multiperiod moral-hazard model when the firm wants to implement high effort in every period but only obtains aggregate information on sales. The sales agent chooses effort each period after observing previous sales, and his incentive responsiveness might change over time. The paper derives conditions under which a linear incentive scheme—a pure commission—dominates a bonus plan and vice versa. A commission is optimal if the agent is most difficult to motivate in the last period. Otherwise, combining the commission with a bonus plan can lower the firm’s cost of providing incentives in earlier periods. The results are robust to different types of cost externalities and demand externalities across periods. However, if the firm obtains intermediate sales information, bonus plans dominate commissions. This paper was accepted by J. Miguel Villas-Boas, marketing.